The Literature Curriculum in Russia: Cultural Nationalism vs. The Cultural Turn - Sarsenov, Karin (Culture Unbound, 2010)
In Western educational systems, the question “Why study literature in school?” has been raised in connection with the theoretical development often summarized as “the cultural turn.” The author strives to contribute to this discussion by examining the development of educational discourse in Russia. During the Soviet period, literature was – together with history – the subject most heavily influenced by the dogmas of Soviet state ideology. As such, literature enjoyed great prestige and was a compulsory and separate subject from the fifth to the eleventh school years. Since 1991, the educational system has undergone radical reform, but the number of hours devoted to literature has not changed significantly. This would suggest that literature still is perceived as an important means of incorporating children into the national and political community. The target of this study is to identify authorities’ specific aims in devoting so much time to literature in school, as well as to elucidate in what way literature is to achieve these aims. Russian guidelines for the development of literature curricula published in the years 1991–2010 are examined to see just how literature is legitimated as a secondary school subject. Based on this material, the author draws conclusions about the rhetorical practices and ideological development of curricular discourse, its relationship to Soviet educational thought and the extent to which the cultural turn has influenced this sphere.